Analisis Kepuasan Konsumen Pada Pelayanan Statistik Terpadu Melalui SKD 2022 (Survei Kebutuhan Data) Di BPS Kabupaten Donggala - Moh Ikhsan S. Korona; Ponirin Ponirin; Muh. Riswandi Palawa (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
PST is the gateway for BPS data dissemination. The services provided through the PST unit are one door or referred to as one gate service. The existence of the PST unit is expected to provide convenience for consumers in finding data and statistical information. The PST service system is divided into 2 (two), namely consumers who come directly to PST and consumers who go online to obtain services. These non-face-to-face or online services can be accessed either through the BPS website, via pst.bps.go.id, the BPS AllStat application (based on Android and iOS), telephone, facsimile, e-mail, or mail. The purpose of implementing SKD 2022 in general is to obtain evaluation material from consumers as an important instrument for improving the quality of data and statistical information and providing good service. Besides that, SKD is also a survey designed by BPS to identify the level of need and level of consumer satisfaction with data and services. The methodology described is divided into three parts, namely the sampling method, data collection method, and data analysis method. Based on the data collection method for all PST SKD organizers, the CAWI method is more widely used, for all PST organizers. This is related to the condition of adapting to new habits which include providing services online or online.